When basal insulin is not enough: successful strategies for insulin intensification in patients with type 2 diabetes mellitus - Elena V. Buryukova; Abdul Jabbar; Svetlana V. Elizarova (Сахарный диабет)
Maintaining glycemic control through intensive clinical management of patients with type 2 diabetes mellitus (T2DM) is well recognized to reduce the risk of diabetes-associated complications. Patients in Russia have high rates of microvascular and macrovascular complications as a result of undiagnosed, untreated, or inadequately treated diabetes, emphasizing the need for better clinical management. The introduction of basal insulin therapy is often necessary for patients with T2DM when oral antihyperglycemic drugs and lifestyle management strategies are no longer effective inmaintaining glycemic targets. However, after initiation of insulin, patients often remain on basal insulin for long periods despite suboptimal glycemic control, and intensification of insulin therapy is frequently necessary. Here, we report on several different insulin intensification strategies available to clinicians and their patients to improve glycemic control and the advantages and disadvantages of each approach. These strategies include the use of short- and long-acting insulins administered either as bolus doses or as premixed insulins. When selecting the most appropriate intensification strategy, clinicians should consider the lifestyle and treatment goals of their patients to help ensure treatment success.